Hopping conduction in (Ni, Co, Mn)O4 prepared by different synthetic routes: Conventional and spark plasma sintering. Issue 18 (15th December 2017) - Han, HyukSu; Lee, Hanchan; Lim, Jiun; Kim, Kang Min; Hong, Yu-Rim; Lee, Jaeseok; Forrester, Jennifer; Ryu, Jeong Ho; Mhin, Sungwook
Abstract: (Ni, Co, Mn)O4 (NMC) oxides were prepared by conventional sintering (CS) and spark plasma sintering (SPS) using micro and nanopowders. Small hoping polaron theory was used in order to investigate effect of processing routes on electrical properties of NMC oxides as negative temperature coefficient (NTC) thermistors. Also, X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) techniques were utilized to analyze compositional and structural effects on the electrical properties of NMC compounds. Hopping conduction in NMC prepared by SPS and CS using nanopowder occurs via variable range hopping (VRH) mechanism, however conduction in NMC prepared by CS using micropowder follows nearest neighboring hopping (NNH) mode. Hopping distance and activation energy for the VRH mode were calculated using corresponding physical model.